Simulated Gastrointestinal Digestion of Chestnut (Castanea sativa Mill.) Shell Extract Prepared by Subcritical Water Extraction: Bioaccessibility, Bioactivity, and Intestinal Permeability by In Vitro Assays - Diana Pinto; Ana Margarida Silva; Stefano Dall’Acqua; Stefania Sut; Anna Vallverdú-Queralt; Cristina Delerue-Matos; Francisca Rodrigues (Antioxidants, 2023)
Chestnut shells (CSs) are an appealing source of bioactive molecules, and constitute a popular research topic. This study explores the effects of in vitro gastrointestinal digestion and intestinal permeability on the bioaccessibility and bioactivity of polyphenols from CS extract prepared by subcritical water extraction (SWE). The results unveiled higher phenolic concentrations retained after gastric and intestinal digestion. The bioaccessibility and antioxidant/antiradical properties were enhanced in the following order: oral < gastric ≤ intestinal digests, attaining 40% of the maximum bioaccessibility. Ellagic acid was the main polyphenol in the digested and undigested extract, while pyrogallol–protocatechuic acid derivative was only quantified in the digests. The CS extract revealed potential mild hypoglycemic (<25%) and neuroprotective (<75%) properties before and after in vitro digestion, along with upmodulating the antioxidant enzymes’ activities and downregulating the lipid peroxidation. The intestinal permeation of ellagic acid achieved 22.89% after 240 min. This study highlighted the efficacy of the CS extract on the delivery of polyphenols, sustaining its promising use as nutraceutical ingredient.